A Study of Model Development of Database Management for Public Health Emergency: a Case Study of Flooding Situation - จิรวัฒนะไพศาล ธิดาพร (Journal of Health Science of Thailand, 2026)
This study was aimed to investigate a model of national database management system for flooding events using in three purposive sampling-provinces in southern of the country. Qualitative analysis was conducted. Chomphon, Surattani, and Nakhon Si Thammarat prrovinces were selected. Public health officers from these provinces were interviewed with structed questionnaires and focus group discussion were also conducted. The results were collected from the answers of questionnaire of 60 samples. The results found that there were four groups of information for national database management of flood of Public Health Emergency Operation Center (PHEOC) which were physical, populations, social, and management. The data in the past five years covered information of appointment points, evacuation points, evacuation routes, and risk areas or risk points. The administer was the Division of Public Health Emergency Management. The key persons from public health offices/hospitals were appointed to record/report required information of floods in this database system. Further study should take the result from this study to apply for the investigation of other types of disaster database management.